Portable x-ray fluorescence spectroscopy geochemical sourcing of Miocene primate fossils from Kenya. Issue 170 (September 2022) - Foecke, Kimberly K.; Hammond, Ashley S.; Kelley, Jay
Abstract: Understanding the biogeography and evolution of Miocene catarrhines relies on accurate specimen provenience. It has long been speculated that some catarrhine specimens among the early collections from Miocene sites in Kenya have incorrect provenience data. The provenience of one of these, the holotype of Equatorius africanus (NHM M16649), was previously revised based on x-ray fluorescence spectroscopy. Here we use nondestructive portable x-ray fluorescence spectroscopy to test the provenience of additional catarrhine specimens that, based on morphology and/or incomplete provenience information, were identified as possibly having been collected at a different site from that recorded at museum accession. We test the hypotheses that two specimens purportedly from the Early Miocene site of Rusinga (KNM-RU 1681 and KNM-RU 1999) are instead from Maboko, three specimens purportedly from the Middle Miocene site of Fort Ternan (KNM-FT 8, KNM-FT 41, and KNM-FT 3318) are instead from Songhor, and one specimen accessioned as being from Songhor (KNM-SO 5352) is from that site. Elemental data reveal that two of the specimens (KNM-FT 3318 and KNM-RU 1681) are likely to have been collected at sites other than their museum-accessioned provenience, while two others (KNM-RU 1999, and KNM-FT 41) were confirmed to have correct provenience. Results for both KNM-FT 8 and KNM-SO 5352, while somewhat equivocal, are best interpreted as supporting their accessioned provenience. Our results have implications for the distribution of certain catarrhine species during the Miocene in Kenya. Confirmation of the provenience of the specimens also facilitates taxonomic attribution, and resulted in additions to the morphological characterizations of some species. The protocol presented here has potential for wider application to assessing questions of provenience for fossils from other locations and periods.